Sprachkritik. - Kilian, J?org (Germanistische Arbeitshefte., 2016)
This workbook provides an introduction to the principles, research questions, and current findings of linguistics-based language criticism. It focuses on three practice areas to present the approaches and methods of critical language observation: linguistics and language philosophy; language didactics and German language instruction; and public and medial reflections on language.